2013
DOI: 10.1606/1044-3894.4326
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Spiritual Needs of Hospitalized Asian Americans: Predictors of Satisfaction among a National Sample of Inpatients

Abstract: Tailoring services to address patients' spiritual needs is widely recognized to be an important component of service provision in health care settings. Yet, despite the growth of the Asian American population, little research has examined predictors of Asian American patients' satisfaction with this process. To address this gap, the present study employed a national sample of Asian Americans (A/ = 2,102) to identify predictors of satisfaction with the manner in which their spiritual needs were addressed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Cherry (2013) found that Catholicism facilitates Filipino American community involvement. Hodge, Bonifas, and Wolosin (2013) reported that Asian American patients were more satisfied with hospitalization when their spiritual needs were addressed. Finally, Kim, Miles-Mason, Kim, and Esquivel (2013) found that daily spiritual experiences of forgiveness and congregational support were significant predictors of life satisfaction in Korean American adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Cherry (2013) found that Catholicism facilitates Filipino American community involvement. Hodge, Bonifas, and Wolosin (2013) reported that Asian American patients were more satisfied with hospitalization when their spiritual needs were addressed. Finally, Kim, Miles-Mason, Kim, and Esquivel (2013) found that daily spiritual experiences of forgiveness and congregational support were significant predictors of life satisfaction in Korean American adolescents.…”
Section: Resultsmentioning
confidence: 99%